Answer:
Explanation:
A graphing calculator shows there is one solution to ...
![\log_7{(3x^2+x)}-\log_7{(x)}=2](https://img.qammunity.org/2021/formulas/mathematics/college/90i4rtsx1ghft4e26oa8yw9dg8tixuk7nx.png)
However, the usual solution method would be to combine the logarithms and take the antilog to get ...
![\log_7{\left((3x^3+x)/(x)\right)}=2\\\\\log_7{(3x^2 +1)}=2\\\\3x^2+1=7^2\\\\x^2=(49-1)/(3)=16\\\\x=\pm 4\qquad\text{take the square root}](https://img.qammunity.org/2021/formulas/mathematics/college/2ch3jl55362zj4na3pmoojk33w5vyw58mu.png)
This gives two solutions. the "solution" x = -4 is extraneous, as it doesn't work in the original equation. "x" must be positive in the log expressions.